Morphological and genetic variation of Leptopelis brevirostris encompasses the little-known treefrogs Leptopelis crystallinoron from Gabon and Leptopelis brevipes from Bioko Island, Equatorial Guinea. Issue 2 (13th December 2019) - Bell, Rayna C; McLaughlin, Patrick J; Jongsma, Gregory FM; Blackburn, David C; Stuart, Bryan L
ABSTRACT: The Central African treefrog Leptopelis brevirostris has a characteristically short and vertically truncated snout, a tooth-like process at the centre of the mandible, and unlike most species of Leptopelis, eats terrestrial gastropods. Two morphologically similar species ( L. crystallinoron and L. brevipes ) have been described in sympatry with L. brevirostris, each on the basis of a single female specimen and then provisionally synonymised with L. brevirostris by subsequent authors. Here we re-examine the holotypes of the three species and collect both genetic (mtDNA and 25 nuDNA loci) and morphological data across the range of L. brevirostris and its sister species L. notatus to test the hypothesis that L. brevirostris is comprised of more than one species. We found that the diagnostic characters for L. crystallinoron (lacking a visible tympanum and having larger vomerine teeth in contact) and L. brevipes (distinctive dorsal colouration) are also present in L. brevirostris and L. notatus . Furthermore, these characters vary among individuals that share the same mitochondrial haplotype and that occur within a single locality, including the type locality of L. crystallinoron . Although all samples from the type locality of L. crystallinoron form a distinct mitochondrial lineage relative to L. brevipes and L. brevirostris, our analysis of 25 nuclear loci does not support this relationship and instead suggests that this mitochondrial divergence reflects phylogeographic structure across the range of L. brevirostris, including samples from the type localities of L. crystallinoron and L. brevipes . By contrast, the mitochondrial divergence between L. notatus and L. brevirostris is strongly supported in the nuDNA dataset. Consequently, we recognise both L. brevipes and L. crystallinoron as synonyms of L. brevirostris . Given the extensive variation in the colour pattern, the tympanic membrane, and the size and shape of the vomerine teeth among L. brevirostris collected from one locality, variation in these traits should be interpreted with caution in taxonomic research on Leptopelis .